2018
DOI: 10.1177/0002764218773829
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst to Connection: When Technical Difficulties Lead to Social Support for Older Adults

Abstract: Information and communication technology (ICT) use can mitigate the negative impact of various age-related threats, such as isolation and loneliness, by facilitating connection with social ties and access to social support. Although research regarding various uses and benefits of ICTs among older adults has increased, there is limited research regarding the impact of technical difficulties on older adults’ well-being. Our study explores technical difficulties encountered, how older adults cope with ICT failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 50 publications
3
41
1
Order By: Relevance
“…Older adults who are not using the internet or digital online services during this pandemic should not be viewed as frail and unwilling to use those digital offers; rather, their decisions should be respected and alternatives should be employed (e.g., writing letters) when possible or support should be offered to them to help them use ICTs. Awareness of the “digital divide” and offerings of ICT support should come, not only from designers, developers, and manufacturers of ICT and internet systems, services, and products, but also from social ties—particularly family members, friends, and neighbors—which may help enhance social support and engagement ( Francis et al, 2018 ). This is crucial for promoting widespread digital inclusion ( Damodaran et al, 2015 ) during COVID-19 and future pandemics.…”
Section: Enhancing Social and Digital Participationmentioning
confidence: 99%
“…Older adults who are not using the internet or digital online services during this pandemic should not be viewed as frail and unwilling to use those digital offers; rather, their decisions should be respected and alternatives should be employed (e.g., writing letters) when possible or support should be offered to them to help them use ICTs. Awareness of the “digital divide” and offerings of ICT support should come, not only from designers, developers, and manufacturers of ICT and internet systems, services, and products, but also from social ties—particularly family members, friends, and neighbors—which may help enhance social support and engagement ( Francis et al, 2018 ). This is crucial for promoting widespread digital inclusion ( Damodaran et al, 2015 ) during COVID-19 and future pandemics.…”
Section: Enhancing Social and Digital Participationmentioning
confidence: 99%
“…When a device ceases to function as it should, ICT maintenance is difficult for many older adults and especially older adults of lower socioeconomic status. Low-SES older adults may lack either the financial means to pay the professionals, such as the Geek Squad, or the social ties to enlist help (Francis, et al, 2018).…”
Section: Agingmentioning
confidence: 99%
“…Receiving technical support can also have positive implications for healthy aging. Several studies point to the importance of social support when technical difficulties occur and that receiving technical support may create opportunities for social connection with loved ones (Barnard et al 2013;Cornejo, Tentori, and Favela 2013;Francis et al 2018;Quan-Haase et al 2017;Tsai et al 2017). On the basis of in-depth qualitative interviews with older adults in a Canadian city, Quan-Haase et al (2017) found that learning how to use technology became a method of garnering social support and even led to strengthened social networks for older adults.…”
Section: Social Support and Help With Technology Usementioning
confidence: 99%